Gelatin-Polyvinyl Alcohol Film for Tissue Engineering: A Concise Review - Izzat Zulkiflee; Mh Busra Fauzi (Biomedicines, 2021)
The field of biomaterials has been steadily expanding as a large number of pharmaceutical and manufacturing companies invest in research in order to commercialize biomaterial products. Various three-dimensional biomaterials have been explored including film, hydrogel, sponge, microspheres etc., depending on different applications. Thus, gelatin and polyvinyl alcohol (PVA) are widely used as a natural- and synthetic-based biomaterial, respectively, for tissue engineering and clinical settings. The combination of these materials has proven its synergistic effects in wound-healing applications. Therefore, this review aims to highlight the hybrid gelatin and PVA thin film development and evaluate its potential characteristics for tissue engineering applications from existing published evidence (within year 2010–2020). The primary key factor for polymers mixing technology might improve the quality and the efficacy of the intended polymers. This review provides a concise overview of the current knowledge for hybrid gelatin and PVA with the method of fabricating and mixing technology into thin films. Additionally, the findings guided to an optimal fabrication method and scrutinised characterisation parameters of fabricated gelatin-PVA thin film. In conclusion, hybrid gelatin-PVA thin film has higher potential as a treatment for various biomedical and clinical applications.